Pendampingan Edukasi Wisata Pesisir Kampung Jenggalu Kito Perspektif Islamic Blue Economy - Zaki, Khozin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
Coastal Indonesia has a close relationship in business development efforts in the field of tourism and various other supporting businesses. To realize a sustainable and ethical economy, coastal areas must be developed in harmony and in line with moral values and religious nobility. Kampung Jenggalu is one of the coastal areas in Bengkulu City where the community together with the locals are trying to develop an eco-edu tourism model. tourism that can provide a unique and interesting natural sensation so that it is suitable as a place for marine tourism. This paper seeks to integrate this potential with the value of the Islamic Blue Economy so that the method used is a form of devotion using the action research paradigm through the planning, action and fact finding stages.Through 3 stages of activity, namely mentoring the concept of coastal tourism, coastal tourism education, Muslim-friendly coastal tourism, guidelines and also Muslim-friendly coastal tourism packages that can be used by the Jenggalu Kito Village to develop their economic level basedon universal Islamic values in economic management tourism-basedcoast.